Bilateral bifid mandibular condyle: Report of a case with condylar fractures - Elif Tarim Ertas; Halil Sahman; Meral Yircali Atici (Wolters Kluwer Medknow Publications, 2013)
Bifid mandibular condyle is an uncommon anatomic variation with a varied etiology implicated with its development. It can be symptomatic or the majority of the cases are diagnosed incidentally during radiographic examination. Bifid mandibular condyle may have a developmental origin or may occur secondary to trauma. The purpose of this paper is to report a case with bilateral bifid mandibular condyles associated with a history of condylar fractures presented with computed tomography and panoramic radiography findings.